2017
DOI: 10.3389/fmicb.2017.01813
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Pure Microbial Systems: Experimental Measurements and Modeling

Abstract: Cellular heterogeneity influences bioprocess performance in ways that until date are not completely elucidated. In order to account for this phenomenon in the design and operation of bioprocesses, reliable analytical and mathematical descriptions are required. We present an overview of the single cell analysis, and the mathematical modeling frameworks that have potential to be used in bioprocess control and optimization, in particular for microbial processes. In order to be suitable for bioprocess monitoring, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 99 publications
(103 reference statements)
2
27
0
1
Order By: Relevance
“…We demonstrated that interactions between bacterial populations lead to an adjustment of the individual phenotypic diversities of the interacting populations. Since phenotypic heterogeneity is playing an important role in pathogenicity and virulence (14), antibiotic resistance (12,54), biotechnological applications (20,23,55,56), and ecosystem properties (57), it is crucial to understand its influencing factors. The experimental design presented here provides a framework within which further ecological hypotheses regarding phenotypic heterogeneity and microbial interactions can be tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that interactions between bacterial populations lead to an adjustment of the individual phenotypic diversities of the interacting populations. Since phenotypic heterogeneity is playing an important role in pathogenicity and virulence (14), antibiotic resistance (12,54), biotechnological applications (20,23,55,56), and ecosystem properties (57), it is crucial to understand its influencing factors. The experimental design presented here provides a framework within which further ecological hypotheses regarding phenotypic heterogeneity and microbial interactions can be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Two laser-based methods that are suitable for assessing phenotypes are flow cytometry and Raman spectroscopy (21)(22)(23). Two types of light can be detected by the flow cytometer: scattered light and fluorescence.…”
mentioning
confidence: 99%
“…We demonstrated that interactions between bacterial populations lead to an adjustment of the individual phenotypic diversities of the interacting populations. As phenotypic heterogeneity is playing an important role in pathogenicity and virulence (14), antibiotics resistance (12, 60), biotechnological applications (20, 23, 61, 62), ecosystem properties (63), it is crucial to understand its influencing factors. The experimental design presented in this study provides a framework within which further ecological hypotheses regarding phenotypic heterogeneity and microbial interactions can be tested.…”
Section: Resultsmentioning
confidence: 99%
“…Two laser-based methods that are suitable for assessing phenotypes are flow cytometry and Raman spectroscopy (2123). Two types of light can be detected by the flow cytometer, that is scattered light and fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Since microbial populations are often complex and consist of a community of multiple species, single‐cell analysis may be vital in dissecting molecular heterogeneity between cells . The applications are wide‐ranging from deciphering phylogenetic trees and evolutionary mechanisms, to discovering novel metabolic features within a microbiome, monitoring and optimizing the productivity in industrial bioprocesses, showing the diversity of symbiotic interactions as well as viral integrations, to elucidating “rare biospheres.” Currently, microbiomes are predominantly categorized by sequencing of the small ribosomal 16S subunit using targeted primers. This targeted technique only amplifies a small proportion of the entire genomic content within a microbial cell, often misses less efficiently amplified rare cells within a population and cannot amplify certain members of the Actinobacteria and Crenarchaeota .…”
Section: Applications Of Single‐cell Technology In Biomedical Researcmentioning
confidence: 99%